2011
DOI: 10.1002/ijch.201100043
|View full text |Cite
|
Sign up to set email alerts
|

Flow Effects in Supramolecular Chirality

Abstract: There are an increasing number of reports on the emergence of circular dichroic signals when solutions of J‐aggregates are vortex‐stirred. Some authors claim that the transfer of chirality from the macroscopic stirring vortex occurs at the level of electronic transitions. Others argue that the signal observed is not due to true circular dichroism (CD), but rather that it is an artifact due to combinations of linear polarization contributions. For both interpretations it is necessary to assume that the alignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…Notice that this chiral effect is not related to the emergence of chirality by vortex stirring previously reported for elongated J-aggregate particles of H 4 TPPS 3 (irreversible effect) [9] or H 4 TPPS 4 (reversible effect), [7,8] which have been attributed to the mechanical deformation of the initially straight particles into chiral folded structures (see refs. [9][10][11]).…”
Section: Resultsmentioning
confidence: 99%
“…Notice that this chiral effect is not related to the emergence of chirality by vortex stirring previously reported for elongated J-aggregate particles of H 4 TPPS 3 (irreversible effect) [9] or H 4 TPPS 4 (reversible effect), [7,8] which have been attributed to the mechanical deformation of the initially straight particles into chiral folded structures (see refs. [9][10][11]).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, mechanical effects may lead to plastic changes in the nanoparticle structure, for example transforming hollow monolayered nanotubes into bilayered ribbons. Despite the lack of enough experimental proofs, elastic changes may occur for some type of particles, e. g. nanotubes under the action of the shear force of laminar flows …”
Section: Discussionmentioning
confidence: 99%
“…Both detection and induction of such chiroptical properties in the intentional absence of a chemical bias have been studied intensely over the past years 16. 20 However, very few researchers paid sufficient attention to the preparation methodology and correlation of the chiroptical response with final morphology of self‐assemblies 21. Recently, it has been shown that the pathway complexity of aggregation of the classic meso ‐tetra(4‐sulfophenyl) (TPPS) porphyrin influences the final chiroptical response 22…”
Section: Introductionmentioning
confidence: 99%